Exploring the use of Information and Communication Technology in Open and Distance Learning: The Case study of Botswana Open University - Magetse, Tebogo; Khoza, Samuel; Naiker, Vasidevan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This qualitative study investigated the utilization of Information and Communication Technology (ICT) in an Open and Distance Learning (ODL) university located in Botswana. The sampling technique employed was judgmental sampling, which involved the selection of 16 participants comprising of a lecturer, students, and officers responsible for managing the Learning Management System (LMS). The data collection process incorporated face-to-face interviews with the lecturer and officers, as well as open-ended e-questionnaires administered to the students. Narrative data analysis was conducted separately for the lecturer, officers, and students. By applying the Attrition theory, the findings disclosed that students of the Botswana Open University encounter challenges with the ODL mode due to limited resources, inadequate or non-existent internet services, and the remoteness of areas where access to BOU campuses is impracticable. According to the lecturers, they also require technical support when assessing students' work, as these students often encounter difficulties when uploading their assignments onto the university's LMS. Consequently, the study recommends that BOU should ensure the availability of ICT tools for the students, as well as address issues related to connectivity and bandwidth by providing reliable data services. Additionally, it is proposed that students undergo comprehensive training on the LMS systems, encompassing both technical and non-technical aspects, prior to the commencement of the academic year, in order to adequately prepare them for their studies.